Seismic inversion and attributes analysis for porosity evaluation of the tight gas sandstones of the Whicher Range field in the Perth Basin, Western Australia - Kadkhodaie-Ilkhchi, R.; Moussavi-Harami, R.; Rezaee, M. Reza; Nabi-Bidhendi, M.; Kadkhodaie-Ilkhchi, A. (ELSEVIER, 2014)
A comprehensive understanding of porosity variations in tight gas sandstones plays an important role in reservoir management and provision of plans for developing of the field. This is especially important when we encounter with some degree of complexity in reservoir characteristics of these sandstones. Reservoir properties of tight gas sandstones of the Whicher Range field, the target reservoir of this study, were affected by internal reservoir heterogeneity mostly related to depositional and diagenetic features of the reservoir sandstones. In this study, 2D seismic data in combination with well log data were used for prediction of porosity based on seismic inversion technique and multi-attribute regression analysis. The results show that acoustic impedance from model based inversion is the main seismic attribute in reservoir characterization of tight sandstones of the field. Wide variations in this parameter can be effectively used to differentiate the reservoir sandstones based on their tightness degree. Investigation of porosity by this method resulted in 2D-view of porosity variations in sandstone reservoir which is in accordance with variations in geological characteristics of tight gas sandstones in the field. This view can be extended to a 3D-view in the framework of reservoir model to follow the variations throughout the field.